Urban Transport and Sustainable Development - Newman, Peter; McIntosh, J.; Matan, Annie (Routledge, 2015)
The idea of sustainable development is highly relevant to the world’s cities. Cities have been the major source of social and economic opportunity for the growing world population for around 8,000 years, but in the last century this has dramatically increased. In this period of industrialization and globalization, the world’s cities have been creating opportunity at the expense of ecological footprint. Growing consumption of resources and the subsequent growth in wastes have had local, regional and global impacts (Newman and Kenworthy 1999). Today cities are responsible for around 40 per cent of the world’s greenhouse gases (GHG). Thus the challenge of sustainable development in cities is how they can continue to play their historic role as providers of social and economic opportunity while reducing, not increasing, their ecological footprint. Put simply, the challenge to the world’s cities is to reduce their ecological footprint while improving liveability (Newman and Kenworthy 1999, Newman 2006).